Comunicação Pública e Democracia: uma entrevista com João Pissarra Esteves - Luz, Ana Javes; Galinari, Fabiana Carvalho; Becker, Camila Lângaro; Stevens, Leandro; Carnielli, Fiorenza Zandonade; Gautier, Tiago (Compolítica, 2015)
Entrevista com João Pissarra Esteves